Disc Plate Method of Microbiological Antibiotic Assay: I. Factors Influencing Variability and Error - Davis, W. W. (1971)
Several factors are investigated that normally cause variation in zone diameters in conventional disc plate diffusion assay procedures. Of these factors the most serious is the unequal exposure of the individual plates at top or bottom of stacks to temperatures above and below room temperature. This unequal temperature exposure is avoided by novel handling and incubation procedures. A major variable, but one which can be controlled, is the varying time interval between pouring seeded agar and the time of applying the pads with antibiotic to the plates. This influence of time of setting and the effects of several other sequential operations are combined into a composite variable. This variable is then accounted for and normalized by interposing “external” reference plates set with a reference solution in the sequence of approximately 100 plates. No “internal” reference zones are employed. Such factors as volume of agar poured, wedge shape of agar in a dish, volumetric errors in dilutions, and timing considerations are studied and discussed. The results of this study form the basis for a test protocol which is presented in a following paper.